1997
DOI: 10.1007/pl00012264
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Composition after Gastrectomy: Results of a Controlled, Prospective Clinical Trial

Abstract: To elucidate mechanisms involved in weight development after gastrectomy we have prospectively determined changes in body composition during the first year after similar operations. A total of 75 patients were enrolled who had a "curative operation" for gastric carcinoma; 42 were randomized to have a total gastrectomy, 23 total gastrectomy with a gastric substitute, and 10 subtotal gastrectomy. All reconstructions were done with a Roux-en-Y loop of the jejunum. Body composition was assessed preoperatively and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 19 publications
4
66
1
6
Order By: Relevance
“…The general extent to which skeletal muscle mass decreases after gastrectomy remains unclear because few body composition studies have been conducted, and no research before our own has used CT image analysis to evaluate changes in skeletal muscle mass following gastrectomy. In this study, the postoperative changes in body composition after TG consisted mainly of the depletion of fat, as seen in previous studies [13][14][15]24]. In fat tissue, a reduction of 56.1 ± 36.4 % in subcutaneous plus intramuscular adipose tissue and a reduction of 77.4 ± 39.0 % in visceral adipose tissue were observed in this study (data not shown).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The general extent to which skeletal muscle mass decreases after gastrectomy remains unclear because few body composition studies have been conducted, and no research before our own has used CT image analysis to evaluate changes in skeletal muscle mass following gastrectomy. In this study, the postoperative changes in body composition after TG consisted mainly of the depletion of fat, as seen in previous studies [13][14][15]24]. In fat tissue, a reduction of 56.1 ± 36.4 % in subcutaneous plus intramuscular adipose tissue and a reduction of 77.4 ± 39.0 % in visceral adipose tissue were observed in this study (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…Although the main postoperative change in body composition after TG is a loss of fat mass, various degrees of skeletal muscle mass reduction have been demonstrated [13][14][15]. Preventing the loss of skeletal muscle mass after TG may lead to improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that weight loss usually occurs early, especially within the first 6 months after surgery, although data on changes in body composition after subtotal gastrectomy are limited (Liedman et al, 1997). Our study showed that body weight, body mass index, waist circumference and body fat percentage were decreased 1 year after subtotal gastrectomy, whereas fat-free mass did not change (Table 2).…”
Section: Jeon Et Al 2004supporting
confidence: 44%
“…The reduction of body fat results in weight loss and reduced body mass index after subtotal gastrectomy. In a study about changes in body composition after gastrectomy, it has been reported that approximately 90% of weight loss is caused by reduced body fat (Liedman et al, 1997). However, the reason why the decrease in body fat is most sensitive among compartments of body composition after gastrectomy is unknown.…”
Section: Jeon Et Al 2004mentioning
confidence: 99%
“…One of the advantages of laparoscopic gastrectomy was reported to be the prevention of overt weight loss, which had generally been explained in terms of decrease in protein mass rather than fat mass [7]. Another study has demonstrated selective loss of fat mass during the first 6 months after open gastrectomy, with a minor decrease of arm circumference [8]. There have been no other longitudinal studies evaluating changes in the composition of the body and extremities after gastrectomy.…”
Section: Introductionmentioning
confidence: 99%